Oligo‐FISH Paints in Triticeae. Issue 2 (14th February 2022) - Li, Guangrong; Yang, Zujun
Abstract: We developed seven oligonucleotide (oligo) pools based on single‐copy sequences, targeting chromosomes 1 to 7 of barley ( Hordeum vulgare L.) and wheat ( Triticum aestivum ) for chromosomal Oligo‐FISH painting methods. The probes were applied to high‐throughput karyotyping for the Triticeae tribe of over 350 species including 30 genera such as Triticum, Hordeum, Secale, Aegilops, Thinopyrum, and Dasypyrum, as well as several wheat alien–derived lines. In combination with other nondenaturing FISH (ND‐FISH) procedures using tandem‐repeat oligos, the newly developed Oligo‐FISH painting technique provides an efficient tool for the identification of individual chromosomes with homologous linkage groups to establish standard karyotypes, particularly with any wild Triticeae species having nonsequenced genomes for chromosome evolutionary analysis. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Oligo‐pool probe development Basic Protocol 2 : Nondenaturing FISH Basic Protocol 3 : Oligo‐FISH painting